The Impact of Reflective Practice on Teacher Candidates' Learning - Slade, Mary L.; Burnham, Tammy; Catalana, Sarah Marie; Waters, Tammy (International journal for the scholarship of teaching and learning, 2019)
Reflection is a high impact practice that develops teacher candidates' learning. Critical reflection requires teacher candidates to continually examine their own thoughts, perspectives, biases, and actions. Reflective practice facilitates the development of new knowledge, skills, and dispositions in teacher candidates by fostering critical contemplation of actions in a real-world environment. Reflective practice is specifically used as teacher candidates study education in a university course and apply what they learn in a related field experience in a K-12 school.This study was conducted in order to determine the impact of reflective practice on teacher candidates enrolled in a course focused on developmental sciences in a context of poverty. Results demonstrate what level of reflection is required to prepare teacher candidates to make instructional decisions as well as become self-aware of their perspectives and attitudes in teaching.